Action research within an elite rugby union coaching group to influence change in coach learning and pedagogic practice. Issue 3 (1st September 2020) - Chapron, James; Morgan, Kevin
ABSTRACT: The aim of this study was to investigate how I, a Welsh regional rugby academy head coach, could utilize practical collaborative action research (CAR) to influence collaboration, learning and pedagogic change within a coaching group. Action research (AR) aims to increase knowledge and improve practice in applied settings and utilises the experiences of the participants as researchers in the field. I acted as head coach and lead researcher with two other professional coaches and two sport science support staff over a three-month period. Data was collected through reflective logs, video observations of training sessions and team meetings. Whilst not without frustrations, difficulties and challenges, qualitative analysis revealed that the coaching team made significant strides in their collaboration, learning and pedagogic practice. Using CAR provided opportunities for the coaching team to develop their motivation, pedagogical knowledge, coaching practice and reflective abilities. Abberivation : CAR - collaborative action research